Puritan’s Hegemony in the Nathaniel Hawthorn’s The Scarlet Letter (Language Circle: Journal of Language and Literature, 2020)
Misperception and inhuman behave presented by Puritan in conducting state administration, consequently character of Hester Prynne in the novel of Nathaniel Hawthorn’s The Scarlet Letter under the implementation of religious values, law assembling, and political system. The implementation of Puritan’s inhuman religious, law and political values to Prynne’s personal character is something criminal behave, and assembling of the law in the case of sin of Prynne’s adultery presented by Custom House was irresponsible decision or immoral severance in front of court. Puritan’s values over the social living is regulated not only for social norms, culture, and law affairs, but even political matters, means that everything must be obeyed and be bent over the God’s rule, and so to whom (married woman) has committed adultery, must be committed as a sinner and impose a sentence in front of general public. It is a library research and used descriptive qualitative analysis. In challenging and lift it up the universal value in against suppressive, hegemonic in the case Prynn the writer used two approachings as solution to solve the problem and they are feminism perspective and deconstruction model as a solution over the Prynne’s problem.